Meningkatkan Kreativitas Anak Melalui Kegiatan Taman Ceria (Belajar Sambil Bermain di Luar Ruangan) di Desa Pasinan Kecamatan Lekok - Nunik Hidayati; Zhunnun Qothrunnada; Farida Nabilah; Uswatun Chasanah; Siti Kholidatur Rodliyah; Mirza Elmy Safira; Nailul Ulah Al Chumairoh Machfud (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2024)
Activities to improve children's creativity through cheerful garden activities (learning while playing outdoors) in Pasinan village, Lekok sub-district, this activity was carried out for approximately five times and for its implementation on Saturdays and Sundays each meeting discussed a different topic. For the first activity in the ceria park, namely making a pigura made from used cardboard with decorations made from tree branches and origami. Providing material about the design of the craft form to be made and making changes to the design of the craft form so that the results obtained can channel the strengths of this cheerful garden program such as minimizing expenses, attracting customer attention by increasing product visuals, and maximizing the ergonomic value of the products created. This community service uses the PAR method and is able to improve the expertise and skills of children in Pasinan village, therefore the expertise possessed by everyone can undergo social change based on involvement in a related activity. The PAR method in community service activities is an activity that has a very significant impact because it focuses on improvement and change.